2019
DOI: 10.3847/1538-4357/ab384d
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Ionization Effects on Coronal Plasma Diagnostics and Elemental Abundance Measurements

Abstract: Plasma diagnostics and elemental abundance measurements are crucial to help us understand the formation and dynamics of the solar wind. Here we use a theoretical solar wind model to study the effect of nonequilibrium ionization (NEI) on plasma diagnostic techniques applied to line intensities emitted by the fast solar wind. We find that NEI almost always changes the spectral line intensities with up to 120% difference for the lighter elements and for higher charge states of Fe even below 1.5 solar radii (R … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Finally, the inverted DEM for the observation requires further discussion as the inversion is an ill-posed problem with various limitations (see, e.g., Aschwanden et al 2015). In Shi et al (2019), we compared three methods and found that the MCMC method, although computationally expensive, can usually achieve a robust and accurate result. However, because the resulting DEM at a certain pixel is only the most probable curve among a batch of Monte Carlo realizations, the inversion result may still have a smooth falloff at high temperatures, even with a plasma temperature cutoff.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the inverted DEM for the observation requires further discussion as the inversion is an ill-posed problem with various limitations (see, e.g., Aschwanden et al 2015). In Shi et al (2019), we compared three methods and found that the MCMC method, although computationally expensive, can usually achieve a robust and accurate result. However, because the resulting DEM at a certain pixel is only the most probable curve among a batch of Monte Carlo realizations, the inversion result may still have a smooth falloff at high temperatures, even with a plasma temperature cutoff.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Interested readers are referred to a review by Aschwanden et al (2015) for more discussions and comparisons of some of the most used inversion methods. In Shi et al (2019), we found that the Markov Chain Monte Carlo (MCMC) method (Kashyap & Drake 1998) generally provides reasonable results. A Markov chain is a stochastic model that defines the transition from one state to the next using a probabilistic approach, and the MCMC method uses an ensemble of such chains to asymptotically determine the best solution, which is usually very robust.…”
Section: Spectroscopic Data For Dem Analysismentioning
confidence: 99%
“…Such effects have direct consequences for diagnostic techniques making use of absolute line intensities or intensity ratios of lines from different ions, such as elemental abundances, plasma thermal distribution, and electron temperature, and can also affect the plasma radiative losses (Landi et al 2012b). It is therefore important to use the nonequilibrium ionization (NEI) assumption in coronal plasma diagnostics, see, e.g., Lee et al (2019), Shi et al (2019), andGilly &Cranmer (2020). Reviews about NEI effects on spectra in the solar atmosphere can be found in, e.g., Bradshaw & Raymond (2013) and Dudík et al (2017).…”
Section: Introductionmentioning
confidence: 99%
“…This transient ionisation in turn can affect other diagnostics, e.g., Refs. [87][88][89]. For a review of transient ionisation conditions, see Ref.…”
Section: Departures From Ionisation Equilibriummentioning
confidence: 99%